An Empirical Study On Artificial Intelligence Based On Digital Marketing For Growth Of Business With Reference To Greater Mumbai (Journal of Namibian Studies : History Politics Culture, 2023)
The online clothes shopping experience is being completely transformed by artificial intelligence (AI). Consumers can enjoy more customized enjoyable purchasing experiences with AI-powered solutions like recommendation engines, virtual try-on capabilities, and personalized product recommendations. By using user preferences, browsing history, and stylistic preferences, these technologies generate recommendations that improve the ease and satisfaction of online shopping. The purpose of conducting this research is to evaluate the impact of AI in online buying of apparel from the perspective of the users. The technique used in this study is one sample t-test. The findings of the study indicated that personalized recommendations, Improved search functions, Virtual try, Chatbots for customer support, Smart shopping carts, AI-powered sizing recommendations, Customization of apparel, Automated price comparison, Personal assistance to users, AI-powered images of the product, Voice search shopping are the significant impact of user’s perspective of AI on Online buying of Apparels.Now more than ever, social media plays a big role in our daily lives. There are many reasons we use social media – to stay updated with news and current events, find entertaining content, fill up spare time, stay in touch with family and friends, play games, or watch online TV and audio streaming.Individuals who master the art of digital marketing use new methods to shape consumer trends through ads seen on social media or videos that inspire consumers to make a purchase with a click of a mouse or tap on a mobile device.Digital marketers create potentially viral content, effective branding strategies, posts that are highly liked or shareable, while generating new leads and anticipating changes in sales trends with persuasive content writing.They can speak to the audience using a simple image or picture that may carry the meaning of a thousand words.Digital marketers can land themselves various exciting career opportunities. In fact, under the Malaysia Digital Economy Blueprint, the government is aiming to provide half a million jobs in the digital economy by 2025, with the digital sector expected to contribute 22.6% to the country’s gross domestic product (GDP).